2022
DOI: 10.1111/afe.12525
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormones in galls on eucalypt trees and in the gall‐forming wasp Leptocybe invasa (Hymenoptera: Eulophidae)

Abstract: 1. The role played by phytohormones in insect galls and the mechanisms underlying plant manipulation by gall makers are still unclear.2. Galls made by Leptocybe invasa on two Eucalyptus species were sampled, the correlations between the levels of nine phytohormones in galls and gall size were analysed, and phytohormone levels in the interior and exterior tissues of galls and L. invasa were determined.3. During two larval stages, the levels of three forms of cytokinins (CKs) in the galls of the two plant specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Based on ELISA and a stomatal-closure bioassay, Heath et al [ 42 ] concluded ABA was present in salivary glands of the flat morph of the gall-inducing Asteromyia carbonifera (Osten Sacken) (Diptera: Cecidomyiidae) at concentrations between 0.5 and 1.5 pmol/g fwt. Wang et al [ 35 ] also reported ABA concentrations in the gall-inducing Leptocybe invasa Fisher & LaSalle (Hymenoptera: Eulophidae) as high as 264 pmol/g fwt based on ELISA assays.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on ELISA and a stomatal-closure bioassay, Heath et al [ 42 ] concluded ABA was present in salivary glands of the flat morph of the gall-inducing Asteromyia carbonifera (Osten Sacken) (Diptera: Cecidomyiidae) at concentrations between 0.5 and 1.5 pmol/g fwt. Wang et al [ 35 ] also reported ABA concentrations in the gall-inducing Leptocybe invasa Fisher & LaSalle (Hymenoptera: Eulophidae) as high as 264 pmol/g fwt based on ELISA assays.…”
Section: Discussionmentioning
confidence: 99%
“…These details will be particularly relevant at the location of insect feeding, but also at larger scales. Finally, given the detection of yet more phytohormones in insect saliva (e.g., SA, JA [ 20 ]) and the detection of JA, GA, and brassinosteroids in a gall-inducing insect species [ 35 ], a more comprehensive examination of non-protein effectors in insect saliva is essential to produce a more complete picture of the repertoire of effectors phytophagous insects may use to manipulate their host plant species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of phytohormones in mediating plant defense responses against insect herbivores has greatly improved in recent years (Erb et al, 2012) There is compelling evidence that gall-induced tissues contain higher concentrations of indole-3-acetic acid (IAA) and/or gibberellins (GAs) compared to non-galled tissues (Takei et al, 2015;Xiang et al, 2020). Galls serve as plant sink organs capable of absorbing nutrients and phytohormones from other plant organs (Hirano et al, 2020).However, the precise role of phytohormones in gall formation remains unknown (Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Galls are known to activate plant reproductive traits to escape immune response and to elicit increased ow of nutrients (Wang et al 2021). Gall inducers reprogram the expression pro les of host plants; they reduce the expression of photosynthesis-related genes and enhance expression of genes related to developmental processes (Favery et al 2020;Martinson et al 2022) by upregulating phytohormones such as auxins and cytokinins (Schultz et al 2019; Tooker and Giron 2020; Wang et al 2022). The g-g wasp system therefore provides us with a unique opportunity to study if pollinators, that act as endophagous resource sinks, are competing with and manipulating the hosts.…”
Section: Introductionmentioning
confidence: 99%